Mirror, Mirror: Framing the Story of Snow White - Gašparovičová, Alena (American & British Studies Annual, 2021)
The Queen’s mirror is an essential part of the classic tale “Little Snow White.” It is the driving force behind Queen’s actions and thus behind the whole plot of the story. In feminist criticism, the mirror is often interpreted as a tool of patriarchy that is meant to pit the female characters against one another. Many authors of modern fairy tale rewritings have thusly adjusted the position of the mirror in the story to show the influence it has on female characters. This paper will discuss two such rewritings, namely “The Tale of the Apple” by Emma Donoghue and “Snow White Learns Witchcraft” by Theodora Goss, focusing on how these two authors change the position of the mirror and what effect this has on the female characters. Despite the differences in the approaches of these two authors, the results of the altered role of the mirror share striking resemblances with regard to the messages their stories convey about female characters in a patriarchal story.